Effects of emotionally oriented parental interventions: a systematic review and meta-analysis - Zahl-Olsen, Rune; Severinsen, Linda; Stiegler, Jan Reidar; Fernee, Carina Ribe; Simhan, Indra; Rekdal, Sondre Sverd; Bertelsen, Thomas Bjerregaard (Frontiers in Psychology, 2023)
Objective: This systematic review and meta-analysis investigates the effects of emotionally oriented parental interventions. Background: Several emotionally oriented parental interventions have been developed during the last decade. Some of these have gained popularity and spread across several continents. The literature is growing and consists of qualitative studies; intervention only, quasi-experimental, case-control studies; and randomized controlled trials. They indicate effects for parents and children. However, no systematic review or meta-analysis has, to our knowledge, summarized the results. Method: Using several search engines, we located 8,272 studies. After abstract and full-text screening, 33 studies were assessed for bias and included in the study. Outcomes for parents and children were extracted and combined into three constructs for parents and two for children. Meta-analyses were conducted for each construct to estimate the effect of the interventions using a robust Bayes meta-analysis. Results: The results indicate the presence of a small to medium effect on parents’ mental health, behavior, and use of emotionally oriented parenting, as well as on children’s internalizing and externalizing difficulties. Most participants were recruited from the general population, and clinical settings were rare. The results show little evidence of publication bias. Conclusion: There is evidence of a small to medium effect of emotionally oriented interventions on parents and children.